On p-adic generalized logistics dynamical systems - Mukhamedov, Farrukh; Wan Rozali, Wan Nur Fairuz Alwani (2011)
In this paper we describe basin of attraction of p-adic dynamical system f(x) = ax(1-x2). Here we consider three major cases with respect to the parametera:|a|p< 1,|a|p=1 and |a|p>1. Attractors in the systems are being investigated to describe the trajectory and the behavior of the function. Moreover, we also describe the Siegel discs of the system, since the structure of the orbits of the system is related to the geometry of the p-adic Siegel discs.